Insights into nasal carriage of Staphylococcus aureus in an urban and a rural community in Ghana - Egyir, B.; Guardabassi, L.; Esson, J.; Nielsen, S.S.; Newman, M.J.; Addo, K.K.; Larsen, A.R. (Public Library of Science, 2014)
The epidemiology of Staphylococcus aureus in the community in Ghana was never investigated prior to this study. The aims of the study were: i) to assess prevalence of nasal S. aureus carriage in Ghanaian people living in an urban and a rural area, and ii) to identify phenotypic and genotypic traits of strains isolated from the two communities. Nasal swabs were collected from healthy individuals living in an urban community situated in the suburb of the capital city, Accra (n = 353) and in a rural community situated in the Dangme-West district (n = 234). The overall prevalence of nasal carriage was 21% with a significantly higher prevalence in the urban (28%) than in the rural community (11%) (p,0.0001). The levels of antimicrobial resistance were generally low (,5%) except for penicillin (91%) and tetracycline (25%). The only two (0.3%) MRSA carriers were individuals living in the urban area and had been exposed to hospitals within the last 12 months prior to sampling. Resistance to tetracycline (p = 0.0009) and presence of Panton-Valentine leukocidin (PVL) gene (p = 0.02) were significantly higher among isolates from the rural community compared to isolates from the urban community. Eleven MLST clonal complexes (CC) were detected based on spa typing of the 124 S. aureus isolates from the two communities: CC8 (n = 36), CC152 (n = 21), CC45 (n = 21), CC15 (n = 18), CC121 (n = 6), CC97 (n = 6), CC30 (n = 5), CC5 (n = 5), CC508 (n = 4), CC9 (n = 1), and CC707 (n = 1). CC8 and CC45 were less frequent in the rural area than in the urban area (p = 0.02). These results reveal remarkable differences regarding carriage prevalence, tetracycline resistance, PVL content and clonal distribution of S. aureus in the two study populations. Future research may be required to establish whether such differences in nasal S. aureus carriage are linked to socio-economic differences between urban and rural communities in this African country.